Frequency of PDGFRA, PDGFRB and FGFR1 Gene Rearrangements in Patients with Eosinophilia and Their Clinico-Haematologic Parameters - Jalil, Saniya; Robert, Helen Mary; Saeed, Hamid; Abbasi, Asad Mehmood; Latif, Aamna; Sardar, Annum (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the frequency and clinico-haematological features of PDGFRA, PDGFRB and FGFR1 gene rearrangements in patients with persistent Eosinophilia using Fluorescence in situ hybridization. Study Design: Cross-sectional study. Place and Duration of Study: Department of Hematology, Armed Forces Institute of Pathology, Rawalpindi Pakistan, from Dec 2018 to Dec 2019. Methodology: All Patients who presented to AFIP having absolute eosinophil count >1.5x109/L persistent for over six months or with Myeloid or Lymphoid neoplasms with persistent Eosinophilia were studied. Patients having reactive Eosinophilia and those on treatment were excluded. Interphase FISH studies were performed. In addition, 2.5ml of sodium heparin blood was taken. After the denaturation of DNA, slides were set up according to standard protocol. FIP1L1/CHIC2/PDGFRA dual colour probe was applied for PDGFRA, 5q32 PDGFRA break apart probe for PDGFRB and XL FGFR1 break apart probe for FGFR1 gene rearrangement. Results: A total of 60 patients were included in the study. Of these, 50(83.3%) were males, and 10(16.7%) were females, with an average absolute Eosinophilia count of 5.92±7.10x109/L. The only rearrangement detected in patients with Eosinophilia was FIPILI-PDGFRA gene fusion, detected in 20% of the patients. No other rearrangement was found. Conclusion: PDGFRA, PDGFRB and FGFR1 mutations are rare yet most prominent in patients with clonal Eosinophilia. About 80% of eosinophilic patients were found to have idiopathic Eosinophilia, which requires further consideration to address the disease prevalence.